Le campane della propaganda: rapporti di reciprocità e conflitto giurisdizionale a Venezia tra Cinque e Seicento - Michaela Valente (Laboratoire Italien)
The author wants to draw attention on the events that followed the Interdict in Venice. She lingers in particular over the presence and the activity –not only diplomatic– of the English and Dutch ambassadors which would have non-Catholic religious functions performed at their homes: in order to announce those functions, they would have the bells rung at length, with the collaboration of the Italians, notwithstanding the nuncio’s opposition.